Efficient Peroral Delivery of Insulin via Vitamin B12 Modified Trimethyl Chitosan Nanoparticles - Ke, Zhiyang; Guo, Han; Zhu, Xi; Jin, Yun; Huang, Yuan (Journal of Pharmacy & Pharmaceutical Sciences, 2015)
PURPOSE: We investigated the effect of vitamin B12 (VB12) modification on the insulin absorption from trimethyl chitosan(TMC) nanoparticles (NPs) under the inﬂuence of mucus. METHODS: TMC and TMC-VB12 were synthesized and insulin loaded TMC/TMC-VB12 nanoparticles were prepared and characterized. Modified and unmodified nanoparticles were studied with Caco-2/HT29-MTX cell model and ligated rat ileum loop. RESULTS: Compared with unmodified NPs, VB12 modified NPs showed signiﬁcantly higher drug internalization in Caco-2/HT29-MTX cell model. The internalization mechanism via VB12 mediation included caveolae and clathrin-mediated endocytosis pathway. Meanwhile, an increased transportation of drugs was observed for VB12 modified NPs, possibly due to the ligand-receptor interaction via an intrinsic factor-dependent fashion. Although the uptake and transport of VB12 modiﬁed NPs could be partially inﬂuenced by mucus, they still showed higher drug permeation through Caco-2/HT29-MTX co-cultured cells than unmodified NPs in the presence or absence of mucus. Moreover, in situ study in ligated rat ileum loop demonstrated that VB12 modiﬁed nanoparticles could reduce the residual insulin in intestinal lumen (0.59 times) and increase their absorption in epithelial tissue (4.8 times) compared with the unmodified ones. CONCLUSION: VB12 modiﬁed trimethyl chitosan nanoparticle is a promising carrier for peroral delivery of insulin. This article is open to POST-PUBLICATION REVIEW. Registered readers (see “For Readers”) may comment by clicking on ABSTRACT on the issue’s contents page.